2022
DOI: 10.1155/2022/9298149
|View full text |Cite
|
Sign up to set email alerts
|

Expression Profiles of Differentially Expressed Circular RNAs and circRNA–miRNA–mRNA Regulatory Networks in SH-SY5Y Cells Infected with Coxsackievirus B5

Abstract: Coxsackievirus B5 (CVB5) is the causative agent of hand, foot, and mouth disease (HFMD) that can cause neurological complications and fatalities. Circular RNA (circRNA) has been shown to play an important role in regulating pathogenic processes. However, the functions of circRNA in response to CVB5 infection remain unclear. In our research, RNA-seq was employed to analyze the expression profiles of circRNAs in SH-SY5Y cells with or without CVB5 infection. Out of 5,665 circRNAs identified to be expressed in SH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Although the precise mechanisms underlying the involvement of circRNAs in antiviral innate and adaptive immune responses and viral pathogenesis are elusive, several studies have revealed their significance. For example, multiple reports have revealed various differentially expressed host circRNAs and established a circRNA–miRNA–mRNA regulatory network in immune responses to infections with multiple viruses, including Hantaan Virus, Human Immunodeficiency Virus, Coxsackievirus B5, Coxsackievirus A16, Rabies Virus, Peste-Des-Petits-Ruminants Virus, Japanese Encephalitis Virus, Porcine Endemic Diarrhea Virus, Pseudorabies Virus Type II, Foot-And-Mouth Disease Virus, Human Papillomavirus E7, Avian Leukemia, Influenza Virus, Infectious Bursal Disease Virus, Enterovirus A71, Swine Hepatitis E Virus, Or Middle East Respiratory Syndrome Coronavirus, SARS-CoV-2 virus, and so on [ 63 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. In addition, plant viruses are also reported to alter circRNAs expression.…”
Section: Involvement Of Circrnas In Innate Immunity Against Viral Inf...mentioning
confidence: 99%
“…Although the precise mechanisms underlying the involvement of circRNAs in antiviral innate and adaptive immune responses and viral pathogenesis are elusive, several studies have revealed their significance. For example, multiple reports have revealed various differentially expressed host circRNAs and established a circRNA–miRNA–mRNA regulatory network in immune responses to infections with multiple viruses, including Hantaan Virus, Human Immunodeficiency Virus, Coxsackievirus B5, Coxsackievirus A16, Rabies Virus, Peste-Des-Petits-Ruminants Virus, Japanese Encephalitis Virus, Porcine Endemic Diarrhea Virus, Pseudorabies Virus Type II, Foot-And-Mouth Disease Virus, Human Papillomavirus E7, Avian Leukemia, Influenza Virus, Infectious Bursal Disease Virus, Enterovirus A71, Swine Hepatitis E Virus, Or Middle East Respiratory Syndrome Coronavirus, SARS-CoV-2 virus, and so on [ 63 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 ]. In addition, plant viruses are also reported to alter circRNAs expression.…”
Section: Involvement Of Circrnas In Innate Immunity Against Viral Inf...mentioning
confidence: 99%